Master batch and method for manufacturing the same
By adding inorganic powder, thermoplastic resin and metal soap to the masterbatch, and using a multi-stage stirring and vacuum treatment extruder process, the stability of masterbatch production, the dimensional changes of molded bodies and the surface roughness problems are solved, and efficient material processing performance is achieved.
Patent Information
- Application Number
- JP2023121408
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
The prior art is difficult to produce masterbatches containing inorganic particles and thermoplastic resins stably and efficiently, and there are dimensional changes and surface roughness problems in the molded body.
Masterbatch formulations containing inorganic powders, thermoplastic resins and metal soaps are employed and processed by a specific extruder process, including multiple stirring sections and vacuum channels to ensure uniform mixing and removal of volatile components, including designs of the first and second stirring sections and the third stirring sections.
The stable production of masterbatches and the low dimensional change rate and appropriate surface roughness of the molded body are achieved, which improves the processing performance and application range of the material.
Smart Images

Figure 2025018026000007 
Figure 2025018026000008 
Figure 2025018026000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a masterbatch and a method for producing the same. [Background technology]
[0002] Today, resin materials in which inorganic fillers and the like are added to petroleum-derived resins are used for various purposes because of their excellent mechanical properties. On the other hand, in areas where scallops and oysters are caught, a large amount of shells are generated after the adductor muscle, uro (guts), and other contents have been removed and discharged. Conventionally, most of these shells have been disposed of in landfills as industrial waste.
[0003] In view of this, as a method for effectively utilizing such shells, it has been proposed to use the shells as an inorganic filler to be added to synthetic resins, as described above (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-75964 A [Patent Document 2] JP 2010-106270 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a method for stably and efficiently producing a masterbatch containing inorganic particles and a thermoplastic resin. [Means for solving the problem]
[0006] The present invention relates to A master batch is provided that includes an inorganic powder, a thermoplastic resin, and a metal soap. The master batch contains inorganic powder having a specific gravity of 2.5 g / cm 3 It could be more than that. In the master batch, the inorganic powder may be shell powder. In the master batch, the shell powder may be scallop shell powder. In the master batch, the inorganic powder may be a mineral powder. In the master batch, the mineral powder may be a clay mineral powder. In the master batch, the clay mineral powder may be talc powder. The thermoplastic resin in the masterbatch may have an MFR of 50 or less. The master batch may have a content of the inorganic powder of 10 mass % or more relative to the mass of the master batch. The present invention relates to There is also provided a molded article molded from a kneaded mixture containing an inorganic powder, a thermoplastic resin, and a metal soap. The molded body has a specific gravity of the inorganic powder of 2.5 g / cm 3 It could be more than that. In the molded body, the inorganic powder may be shell powder. In the molded body, the inorganic powder may be a mineral powder. In the molded body, the mineral powder may be a clay mineral powder. The molded article may have a dimensional change rate of 0.2% or less when placed in an environment at a temperature of 23° C. and a humidity of 50% for one day. The molded article may have a dimensional change rate of 0.2% or less when placed in an environment at a temperature of 23° C. and a humidity of 50% for 3 days. The molded article may have a surface roughness (Ry) of 7 μm or more on at least one surface. The present invention relates to A method for producing a masterbatch using an extruder, comprising the steps of: The extruder includes a first raw material supply port for supplying raw materials of the master batch into a cylinder, a first kneading section provided downstream of the first raw material supply port and kneading the raw materials, a first vacuum vent port provided downstream of the first kneading section, a second kneading section provided downstream of the first raw material supply port and kneading the raw materials kneaded in the first kneading section, a second vacuum vent port provided downstream of the second kneading section, a third kneading section provided downstream of the second vacuum vent port and kneading the raw materials kneaded in the second kneading section, and a discharge port for discharging the raw materials kneaded in the third kneading section, The raw materials include an inorganic powder, a metal soap, and a thermoplastic resin, the first raw material supply port supplies the inorganic powder, the metal soap, and the thermoplastic resin; The present invention also provides a method for producing a masterbatch, in which the degree of kneading in the second kneading zone is stronger than the degree of kneading in the first kneading zone. In the method for producing a masterbatch, the extruder may further include a second raw material supply port provided downstream of the first vacuum vent port and for supplying raw materials for the masterbatch. In the method for producing a masterbatch, the second raw material supply port can supply the inorganic powder and the metal soap. Effect of the Invention
[0007] According to the present invention, it is possible to provide a method for stably and efficiently producing a masterbatch containing an inorganic powder and a thermoplastic resin. The effects of the present invention are not necessarily limited to the effects described herein, and may be any of the effects described in this specification. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a conceptual diagram showing an apparatus used in the method for producing a masterbatch of the present invention. [Diagram 2] FIG. 13 is a graph showing the change over time in the rate of dimensional change in the long side direction of the sheet of Example 5 and the sheet of Comparative Example 1. [Diagram 3] FIG. 13 is a graph showing the change over time in the dimensional change rate in the short side direction of the sheet of Example 5 and the sheet of Comparative Example 1. [Figure 4] FIG. 1 is a schematic diagram showing an example of a multi-layer co-extrusion molding machine used in the production of the multi-layer sheet of Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Preferred embodiments for carrying out the present invention will be described below. Note that the embodiments described below are representative embodiments of the present invention, and the scope of the present invention is not limited to these embodiments.
[0010] The present invention will be described in the following order. 1. First embodiment (1) Masterbatch composition (2) Manufacturing method of master batch 2. Second embodiment (1) Structure of the molded body (2) Method for manufacturing molded body 3. Working Example
[0011] 1. First embodiment
[0012] (1) Masterbatch composition
[0013] The masterbatch according to this embodiment includes an inorganic powder, a thermoplastic resin, and a metal soap. Each component will be described below.
[0014] [Inorganic powder]
[0015] Examples of inorganic powders include shell powder, mineral powder, etc. The specific gravity of the inorganic powder used in the master batch of this embodiment is preferably 2.5 g / cm 3 More preferably, 2.55 g / cm 3 More preferably, 2.6 g / cm 3 More preferably, 2.65 g / cm 3It may be more than that. Shell powder refers to a product obtained by crushing shells into a powder. The shells are not particularly limited, and shells of shellfish such as scallops, oysters, surf clams, abalone, mussels, clams, and mussels can be used. Shell powder may be obtained, for example, by washing and sterilizing shells discarded from food factories and then crushing them, or may be obtained from shells of shellfish other than those used for food. The method for crushing shells is not particularly limited, and any known crushing method may be appropriately selected and adopted, and may be wet or dry. In addition, the shells may be pre-crushed in a coarse crusher and then powdered in a crusher. Specifically, examples of the coarse crusher include jaw crushers, cone crushers, cutter mills, and hammer crushers, and examples of the crushers include roll mills, stamp mills, hammer mills, ball mills, vibrating ball mills, roller mills, and vertical mills. The shell powder may preferably be scallop shell powder. Examples of scallop shell powder include unbaked scallop shell powder and baked scallop shell powder. Unbaked scallop shell powder is made by powdering natural scallop shells and is in an unbaked state that has not been baked, and is usually composed mainly of calcium carbonate (about 96%). Unbaked scallop shell powder is commercially available.
[0016] Examples of mineral powders include clay mineral powders. Both natural and synthetic clay mineral powders can be used. Examples of clay mineral powders include talc (magnesium silicate) powder, kaolin (aluminum silicate) powder, saponite (magnesium aluminum silicate) powder, sericite (microcrystalline potassium aluminum silicate) powder, mica (potassium aluminum silicate) powder, and boron nitride powder. Among these, talc powder is particularly preferred. In addition, as the inorganic powder of this embodiment, only shell powder may be used, or only mineral powder may be used, or shell powder and mineral powder may be mixed and used.
[0017] From the viewpoint of improving the mixability with other components contained in the master batch, the inorganic powder may have an average particle size of preferably 1 to 100 μm, more preferably 5 to 50 μm, and even more preferably 10 to 20 μm.
[0018] When the masterbatch according to this embodiment is used after diluting with another thermoplastic resin, the content of the inorganic powder may be preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the mass% of the masterbatch. The upper limit of the content of the inorganic powder may be, for example, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less, based on the mass% of the masterbatch, taking into consideration the physical properties of the molded product molded using the masterbatch. Furthermore, when the masterbatch according to this embodiment is used as is without diluting it with another thermoplastic resin, the content of the inorganic powder may be preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the mass% of the masterbatch. The upper limit of the content of the inorganic powder may be, for example, preferably 75% by mass or less, more preferably 65% by mass or less, and even more preferably 55% by mass or less, based on the mass% of the masterbatch, taking into consideration the physical properties of the molded product molded using the masterbatch.
[0019] [Thermoplastic resin]
[0020] In the present embodiment, the thermoplastic resin is not particularly limited, but may be preferably a polyolefin-based resin, a polyester-based resin, or a mixture of these resins. The thermoplastic resin may be a polystyrene-based resin.
[0021] A polyolefin resin is a polymer obtained by polymerization of olefins (e.g., α-olefins) as the main monomers. The polyolefin resin may be, for example, a polyethylene (PE) resin, a polypropylene (PP) resin, or a combination thereof.
[0022] The polyethylene resin may be, for example, a low density polyethylene resin (LDPE: Low Density Polyethylene), a high density polyethylene resin (HDPE: High Density Polyethylene), a very low density polyethylene resin (VLDPE: Very Low Density Polyethylene), a linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene), or an ultra high molecular weight polyethylene resin (UHMW-PE: Ultra High Molecular Weight-Polyethylene), or a combination thereof. In addition, the masterbatch used by diluting with another thermoplastic resin preferably has an inorganic powder content of 50% by mass or more relative to the mass of the masterbatch, and from the viewpoint that it is difficult to extrude as a strand from the extruder, and even if a strand is obtained, the strength of the molded body is also poor, a thermoplastic resin having an MFR of preferably 50 or less, more preferably 45 or less, even more preferably 40 or less, and even more preferably 35 or less may be used. When forming a sheet from the masterbatch, from the viewpoint of suppressing drawdown of the obtained sheet, it is preferable to contain a high density polyethylene resin (HDPE: High Density Polyethylene) as the thermoplastic resin.
[0023] The polypropylene resin may be, for example, a homopolymer polypropylene resin, or a random copolymer or block copolymer polypropylene resin (e.g., ethylene-propylene copolymer, etc.), or a combination thereof. In addition, the master batch used by diluting with another thermoplastic resin preferably has an inorganic powder content of 50% by mass or more relative to the mass of the master batch, and from the viewpoint that it is difficult to extrude as a strand from an extruder, and even if a strand is obtained, the strength of the molded body is also poor, a polypropylene resin having an MFR of preferably 50 or less, more preferably 45 or less, even more preferably 40 or less, and even more preferably 35 or less may be used.
[0024] The polyolefin resin may be a polyolefin resin produced using a metallocene catalyst, i.e., the thermoplastic resin may be, for example, a metallocene-catalyzed polyethylene resin or polypropylene resin, or a combination thereof.
[0025] The polystyrene resin may also be a metallocene catalyst-based polystyrene resin.
[0026] The polyester resin is a polymer in which monomers are polymerized through ester bonds. The polyester resin may be, for example, polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polylactic acid resin (PLA), polycarbonate resin (PC), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these.
[0027] Polystyrene resins are polymers formed by polymerization of styrene monomers. Examples of the polystyrene resins include polystyrene resins, rubber-reinforced polystyrene resins (high impact polystyrene resins, HIPS), acrylonitrile-styrene copolymers (AS resins), methacrylate ester-styrene copolymers, acrylonitrile-acrylic rubber-styrene copolymers, and acrylonitrile-ethylene propylene-styrene copolymers, or combinations of two or more of these.
[0028] In this embodiment, the type of thermoplastic resin may be appropriately selected by a person skilled in the art depending on, for example, the type of molded article formed from the masterbatch, but a thermoplastic resin having a low processing temperature is preferred. For example, when a film or sheet is formed from the masterbatch, the thermoplastic resin may be, for example, preferably a polyolefin resin, more preferably a polyethylene resin or a polypropylene resin, and even more preferably LLDPE or LDPE.
[0029] In this embodiment, the thermoplastic resin preferably has a melting point of 90° C. to 180° C., and more preferably has a melting point of 95° C. to 170° C. By using a thermoplastic resin with a lower melting point, the molding temperature can be lowered.
[0030] The thermoplastic resin may be in the form of pellets. From the viewpoint of physical properties and the appearance of the product, the average particle size of the pellets is preferably in the range of 1 to 10 mm on the major axis and 1 to 10 mm on the minor axis.
[0031] When the masterbatch according to the present embodiment is used by diluting it with another thermoplastic resin, the content of the thermoplastic resin may be preferably less than 50 mass %, more preferably 45 mass % or less, and even more preferably 40 mass % or less, relative to the mass of the masterbatch. Furthermore, when the masterbatch according to the present embodiment is used as is without being diluted with another thermoplastic resin, the content of the thermoplastic resin may be preferably less than 80 mass %, more preferably 70 mass % or less, and even more preferably 60 mass % or less, relative to the mass of the masterbatch.
[0032] [Metal soap]
[0033] The metal soap is considered to have a function of improving the dispersibility of the inorganic powder. The metal soap refers to a fatty acid metal salt in which a fatty acid such as palmitic acid, stearic acid, oleic acid, myristic acid, or lauric acid is bonded to a metal such as aluminum, calcium, magnesium, zinc, or barium. Such metal soap may be a commercially available metal soap, and more specific examples include calcium palmitate, lithium palmitate, barium palmitate, aluminum palmitate, zinc palmitate, magnesium palmitate, calcium stearate, lithium stearate, barium stearate, aluminum stearate, zinc stearate, magnesium stearate, calcium oleate, lithium oleate, barium oleate, aluminum oleate, zinc oleate, magnesium oleate, calcium myristate, lithium myristate, barium myristate, aluminum myristate, zinc myristate, magnesium myristate, calcium laurate, lithium laurate, barium laurate, aluminum laurate, zinc laurate, magnesium laurate, etc., and one metal soap selected from these can be used alone or two or more metal soaps can be used in combination. In this embodiment, it is particularly preferable to use magnesium stearate from the viewpoint of improving the dispersibility of the inorganic powder.
[0034] From the viewpoint of improving the dispersibility of the inorganic powder, the content of the metal soap may be preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on the mass% of the masterbatch. From the viewpoint of smoothly extruding the masterbatch from the extruder, the content of the metal soap may be preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the mass% of the masterbatch. From the viewpoint of improving the dispersibility of the inorganic powder, the content of magnesium stearate may be preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on the mass% of the masterbatch. The upper limit of the content of magnesium stearate is not particularly limited, but may be preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less.
[0035] [Other additives]
[0036] It is preferable to select and use additives so that the masterbatch manufacturing method of this embodiment can provide a uniform, homogeneous masterbatch with little variation, so that a material having moldability in various molding methods and excellent workability can be obtained, and so that the material can be suitably processed and used for various applications, such as food containers, packaging materials such as sheets and films, cushioning materials, daily necessities, agricultural products, etc. In this case, in addition to the inorganic powder, thermoplastic resin, and metal soap, various additives are selected according to each application and the required physical properties and functions, and one or more types can be added in combination within a range that does not impair the object of the present invention.
[0037] In this embodiment, a compatibilizer may not be added, but may be added to further improve the affinity between the inorganic powder and the thermoplastic resin. Examples of the compatibilizer that can be used include acid-modified polyolefin, acid-modified nylon, acid-modified polystyrene, acid-modified EVA, acid-modified ethylene copolymer, acid-modified acrylate, acrylic acid-modified EVA, and modified ethylene acrylate.
[0038] As additives used to manufacture a molded product through the master batch obtained by this embodiment, a colorant may not be added, but colorants such as titanium oxide, carbon black, dyes, pigments, etc. may be used as necessary. In addition, additives such as elastomers, antioxidants, crosslinking agents, ultraviolet absorbers, and foaming agents may be appropriately added as necessary.
[0039] (2) Manufacturing method of master batch
[0040] The method for producing a masterbatch according to this embodiment will be described below with reference to Fig. 1. Fig. 1 is a schematic diagram of an extruder 10 used in this embodiment. The extruder 10 includes a cylinder 11 having a cylindrical shape. The cylinder 11 houses a screw (not shown) inside. The extruder 10 includes, from the upstream side, a first kneading section 18, a first vacuum vent port 14, a second kneading section 19, a second vacuum vent port 15, a third kneading section 20, and a third vacuum vent port 16 between a first raw material supply port 12 located at the upstream end of the cylinder 11 and a discharge port 17 for discharging the raw material located at the downstream end. The extruder 10 may further include a second raw material supply port 13.
[0041] The inorganic powder, the metal soap, and the thermoplastic resin may be supplied from the first raw material supply port 12 into the cylinder 11. When the extruder 10 further includes a second raw material supply port 13, the inorganic powder and the metal soap, which are the powder raw materials, may be supplied from the second raw material supply port 13 into the cylinder 11. The ratio of the supply amount of the inorganic powder and the metal soap, which are the powder raw materials, supplied from the first raw material supply port 12 into the cylinder 11 may be divided and supplied, preferably at least 10 mass%, more preferably at least 30 mass%, even more preferably at least 40 mass%, and even more preferably at least 50 mass%, based on the total mass of the inorganic powder and the metal soap supplied. The upper limit of the ratio of the supply amount of the inorganic powder and the metal soap, which are the powder raw materials, supplied from the first raw material supply port 12 into the cylinder 11 may be preferably at most 100 mass%, more preferably at most 90 mass%, even more preferably at most 80 mass%, and even more preferably at most 70 mass%, based on the total mass of the inorganic powder and the metal soap supplied.
[0042] The inorganic powder, the metal soap, and the thermoplastic resin supplied from the first raw material supply port 12 into the cylinder 11 are heated and transferred into the first kneading section 18. In the first kneading section 18, a screw is built in so as to be rotatable (freely rotatable) by a rotary drive mechanism, and the inorganic powder, the metal soap, and the thermoplastic resin are mixed with the screw while being heated and kneaded to obtain a kneaded product. The screw may have a screw shaft and a plurality of screw elements. In the first kneading section 18, a plurality of blocks each having a plurality of screw elements as one unit may be provided. In the first kneading section 18, the heating and kneading temperature may be preferably 140° C. or higher, more preferably 160° C. or higher, even more preferably 180° C. or higher, and even more preferably 200° C. or higher. In the first kneading section 18, the heating and kneading temperature may be preferably 300° C. or lower, more preferably 280° C. or lower, even more preferably 260° C. or lower, and even more preferably 240° C. or lower.
[0043] When the extruder 10 further includes a second raw material supply port 13, the inorganic powder and the metal soap supplied from the second raw material supply port 13 into the cylinder 11 are mixed with the kneaded product obtained in the first kneading section 18, heated, and transferred to the second kneading section 19. In the second kneading section 19, a screw is also built in so as to be rotatable (rotatable freely) by a rotary drive mechanism, as in the first kneading section 18, and the inorganic powder, the metal soap, and the kneaded product are mixed and heated and kneaded by the screw. The screw may include a screw shaft and a plurality of screw elements. In the second kneading section 19, a plurality of blocks each having a plurality of screw elements as one unit may be provided. In the second kneading section 19, the heating and kneading temperature may be preferably 120° C. or higher, more preferably 130° C. or higher, even more preferably 140° C. or higher, and even more preferably 150° C. or higher. In the second kneading section 19, the heating and kneading temperature may be preferably 230° C. or less, more preferably 210° C. or less, even more preferably 190° C. or less, and even more preferably 170° C. or less.
[0044] The degree of kneading in the second kneading section 19 may be stronger than the degree of kneading in the first kneading section 18. The kneaded material kneaded in the second kneading section 19 is heated and transferred to the third kneading section 20. In the third kneading section 20, a screw is built in so as to be rotatable (rotatable freely) by a rotary drive mechanism, and the kneaded material is heated and kneaded while being mixed with the screw. The screw may have a screw shaft and a plurality of screw elements. In the third kneading section 20, a plurality of blocks each having a plurality of screw elements as one unit may be provided. In the third kneading section 20, the heating and kneading temperature may be preferably 80° C. or higher, more preferably 100° C. or higher, even more preferably 120° C. or higher, and even more preferably 140° C. or higher. In the third kneading section 20, the heating and kneading temperature may be preferably 220° C. or lower, more preferably 200° C. or lower, even more preferably 180° C. or lower, and even more preferably 160° C. or lower.
[0045] The mixture kneaded in the third kneading section 20 is discharged from the discharge port 17 to form strands. The first vacuum vent port 14, the second vacuum vent port 15, and the third vacuum vent port 16 are connected to a vacuum pump, which sucks and removes volatile components and the like generated in the cylinder 11 during kneading. The strands discharged from the discharge port 17 are cooled, and then guided to a pelletizer and pelletized to obtain a master batch.
[0046] 2. Second embodiment
[0047] (1) Structure of the molded body
[0048] The molded body according to this embodiment may be molded from a master batch containing an inorganic powder, a thermoplastic resin, and a metal soap. The molded body according to this embodiment may be molded from a kneaded product containing an inorganic powder, a thermoplastic resin, and a metal soap. The molded body according to this embodiment may have a specific range for the dimensional change rate and surface roughness described below. The description of each component in the first embodiment described in 1.(1) above applies to details of each component contained in the master batch for molding the molded body. Therefore, the description of each component will be omitted.
[0049] (Dimensional change rate)
[0050] The molded article according to this embodiment may have a dimensional change rate of preferably 0.2% or less, more preferably 0.15% or less, and even more preferably 0.1% or less when left for one day in an environment at a temperature of 23° C. and a humidity of 50%. Also, the molded article according to this embodiment may have a dimensional change rate of preferably 0.2% or less, more preferably 0.15% or less, and even more preferably 0.1% or less when left for three days in an environment at a temperature of 23° C. and a humidity of 50%.
[0051] The dimensional change rate is the dimensional change rate in at least one of the long side direction and the short side direction of a sheet (molded product) having dimensions of long side 32 cm × short side 14 cm × thickness 0.4 mm. The dimensional change rate was measured by measuring the dimensions in the long side direction and the short side direction when the sheet was left for 1 day, 2 days, and 3 days under conditions of a temperature of 23°C and a humidity of 50%, and calculating the dimensional change rate from the measured dimensions. The dimensional change rate was calculated by the following formula. Dimensional change rate (%) = [L1-L0] / L0 x 100 Here, L1 is the dimension measured after standing, and L0 is the dimension measured before standing began.
[0052] The measurement results of the dimensional change rate are shown in Figures 2 and 3. As shown in Figures 2 and 3, the dimensional change rate in the long side direction and short side direction of the sheet of Example 1 was 0.2% or less over one day and three days. This result shows that the sheet of Example 1 has excellent dimensional stability.
[0053] (Surface roughness)
[0054] In order to obtain good releasability, the molded article according to this embodiment has a surface roughness (maximum height Ry) in the MD direction on at least one surface of preferably 7 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more. Also, the surface roughness (maximum height Ry) in the TD direction on at least one surface of preferably 7 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and even more preferably 20 μm or more.
[0055] The surface roughness (maximum height Ry) of the molded article according to this embodiment may be calculated, for example, in accordance with JIS B0031.
[0056] In order to obtain good releasability, the molded article according to this embodiment has a surface roughness (arithmetic mean roughness Ra) in the MD direction on at least one surface of preferably 1.0 μm or more, more preferably 2.0 μm or more, even more preferably 2.5 μm or more, and even more preferably 3.0 μm or more. Also, the surface roughness (arithmetic mean roughness Ra) in the TD direction on at least one surface of preferably 1.0 μm or more, more preferably 2.0 μm or more, even more preferably 2.5 μm or more, and even more preferably 3.0 μm or more.
[0057] The surface roughness (arithmetic mean roughness Ra) of the molded body according to this embodiment may be calculated, for example, in accordance with JIS B0031.
[0058] Furthermore, in order to obtain good releasability, the molded article according to this embodiment has a surface roughness in the MD direction (ten-point average roughness Rz) of at least one surface of preferably 9.0 μm or more, more preferably 10.0 μm or more, even more preferably 11.0 μm or more, and even more preferably 12.0 μm or more. Also, the surface roughness in the TD direction (ten-point average roughness Rz) of at least one surface of preferably 9.0 μm or more, more preferably 10.0 μm or more, even more preferably 11.0 μm or more, and even more preferably 12.0 μm or more.
[0059] The surface roughness (arithmetic mean roughness Rz) of the molded body according to this embodiment may be calculated, for example, in accordance with JIS B0031.
[0060] (2) Method for manufacturing molded body
[0061] In this embodiment, the master batch is molded to obtain a molded body. For example, the master batch pellets obtained by the master batch manufacturing method are transferred to a molding machine, and the master batch pellets are molded using the molding machine to form a molded body such as a film or sheet. The master batch pellets having an inorganic powder content of preferably 50% by mass or less may be used as is without diluting with other thermoplastic resins, and the master batch pellets having an inorganic powder content of preferably 55% by mass or more may be diluted with other thermoplastic resins to obtain a resin composition, and the resin composition may be molded. The inorganic powder content in the master batch used as is without diluting with other thermoplastic resins may be preferably 5 to 75% by mass, more preferably 10 to 65% by mass, and even more preferably 20 to 55% by mass. The shell powder content in the master batch used after diluting with other thermoplastic resins may be preferably 50 to 95% by mass, more preferably 60 to 90% by mass, and even more preferably 70 to 85% by mass. The molding of a film or sheet is called film formation. The temperature when molding the film or sheet may be set preferably to a temperature equal to or higher than the melting temperature of the thermoplastic resin contained in the masterbatch, for example, 110° C. to 200° C. The molding pressure may also be appropriately set.
[0062] In forming a film or sheet, various film forming machines such as a T-die extruder, a calendar molding machine, and an inflation molding machine can be used. As an inflation molding machine, for example, a ring die can be used. After the molding is formed into, for example, a film-like or sheet-like shape by the film forming machine, the temperature of the take-up roll is appropriately set immediately after the film is formed, and the film or sheet formed to a predetermined thickness is cooled, and taken up and wound as a raw roll. The film refers to a thin film-like material, and the thickness of the film can be, for example, less than 100 μm. The sheet refers to a material thicker than a film, and the thickness of the sheet can be, for example, 100 μm or more. The film or sheet may be a single-layer film or sheet composed only of a layer formed from the master batch, or may be a multilayer film or sheet in which at least one layer formed from the master batch and at least one layer formed from another composition (particularly a resin composition) are laminated. In addition, when molding a molded body other than a film or a sheet, a blow molding machine, an injection molding machine, a thermoforming machine, or a profile extrusion molding machine may be used. For example, a bottle container can be molded by the blow molding machine. For example, a bottle cap or a container can be manufactured by the injection molding machine. For example, a plastic cardboard can be molded by the profile extrusion molding machine.
[0063] In the molding, for example, the masterbatch may be extruded as strands from a film-forming machine or a molding machine without being pelletized, or the pelletized masterbatch may be melted and the molten masterbatch may be extruded from a film-forming machine or a molding machine. The extrusion temperature may be appropriately selected by a person skilled in the art depending on the type and content of the thermoplastic resin contained in the masterbatch.
[0064] 3. Working Example
[0065] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0066] [Example 1]
[0067] 1.Masterbatch manufacturing
[0068] The master batch was supplied to the first raw material supply port 12 of the extruder 10 shown in Fig. 1 so that the scallop shell powder was 20 to 40 mass%, the magnesium stearate was 0.5 to 1.5 mass%, and the zinc stearate was 0.3 to 1 mass% relative to the mass of the master batch. The master batch was supplied to the first raw material supply port 12 so that the polypropylene resin (Qualia (registered trademark) CS356M, manufactured by Sunallomer) was 10 mass%, the polypropylene resin (Noblen (registered trademark) FH1016, manufactured by Sumitomo Chemical Co., Ltd.) was 28 mass%, the compatibilizer was 2 mass%, and other additives were 2 mass% relative to the mass of the master batch. These raw materials were melt-kneaded in the first kneading section 18. The master batch was prepared so that the scallop shell powder was 5-20% by mass, the magnesium stearate was 0.3-1% by mass, and the zinc stearate was 0.1-0.5% by mass. The mixture was fed to the second raw material feed port 13 of the extruder shown in FIG. 1, and transferred to the second kneading section 19 and the third kneading section 20 together with the mixture melt-kneaded in the first kneading section 18. The mixture was further melt-kneaded in the second kneading section 19 and the third kneading section 20, cooled with water, and then fed to a pelletizer to pelletize the mixture to obtain a master batch. The content of the scallop shell powder in the obtained master batch was 51% by mass. When the master batch was produced, the material supply did not stop due to powder blocking.
[0069] The extruder 10 used was a twin-screw extruder (manufactured by Placo, 58 mm, L / D=52). The screw speed of the extruder 10 was 300-500 rpm. The temperature in the cylinder 11 was set from the upstream side to the downstream side of the extruder 10 at 200°C to 300°C in the region from the first raw material supply port 12 to the downstream end of the first kneading section 18, at 150°C to 300°C in the region from the downstream end of the first kneading section 18 to the upstream end of the second kneading section 19, at 100°C to 200°C in the region from the upstream end of the second kneading section 19 to the downstream end of the third kneading section 20, and at 100°C to 200°C in the region from the downstream end of the second kneading section 19 to the discharge port 17.
[0070] [Example 2]
[0071] A master batch was obtained in the same manner as in Example 1, except that the scallop shell powder was 40 to 60 mass%, the magnesium stearate was 1 to 2 mass%, and the zinc stearate was 0.5 to 1 mass% relative to the mass of the master batch, and the master batch was supplied to the first raw material supply port 12 of the extruder 10 shown in FIG. 1, that a polypropylene resin (product name: PM900C, manufactured by SunAllomer) was used instead of the polypropylene resin used in Example 1, and the polypropylene resin (product name: PM900C, manufactured by SunAllomer) was 20 to 30 mass% relative to the mass of the master batch, and the master batch was supplied to the first raw material supply port 12, and that the scallop shell powder was 10 to 30 mass%, the magnesium stearate was 0.5 to 1.5 mass%, and the zinc stearate was 0.3 to 1 mass% relative to the mass of the master batch, and the master batch was supplied to the second raw material supply port 13 of the extruder shown in FIG. 1. The content of the scallop shell powder in the obtained master batch was 70 mass%. When producing the master batch, there was no interruption in the supply of materials due to powder blocking.
[0072] [Example 3]
[0073] A masterbatch was obtained in the same manner as in Example 1, except that a polypropylene resin (product name: AX564E2, manufactured by Sumitomo Chemical Co., Ltd.) was used instead of the polypropylene resin used in Example 1, the content of the polypropylene resin (product name: AX564E2, manufactured by Sumitomo Chemical Co., Ltd.) was 30 to 50 mass% relative to the mass of the masterbatch, and no other additives were added. The content of scallop shell powder in the obtained masterbatch was 51 mass%. When producing the masterbatch, there was no interruption in the supply of materials due to powder blocking.
[0074] [Example 4]
[0075] A masterbatch was obtained in the same manner as in Example 1, except that the masterbatch was supplied to the first raw material supply port 12 of the extruder 10 shown in FIG. 1 so that the scallop shell powder was 30 to 50% by mass, the magnesium stearate was 1 to 2% by mass, and the zinc stearate was 0.5 to 1.5% by mass, relative to the mass of the masterbatch; instead of the polypropylene resin used in Example 1, the masterbatch was supplied to the first raw material supply port 12 so that the masterbatch contained 20% by mass of linear low-density polyethylene resin (product name: SP0540, manufactured by Prime Polymer Co., Ltd.), 11.1% by mass of polyethylene resin (Novatec (registered trademark) LJ902, manufactured by Japan Polyethylene Corporation), and 2.5% by mass of a compatibilizer; and the masterbatch was supplied to the second raw material supply port 13 of the extruder shown in FIG. 1 so that the masterbatch contained 10 to 30% by mass of scallop shell powder, 0.5 to 1.5% by mass of magnesium stearate, and 0.3 to 1% by mass of zinc stearate, relative to the mass of the masterbatch. The content of scallop shell powder in the obtained master batch was 60 mass %. During the production of the master batch, there was no interruption in the supply of materials due to powder blocking.
[0076] [Example 5]
[0077] 2. Sheet manufacturing
[0078] The master batch of Example 1 was mixed at 95% by mass, high density polyethylene resin (product name: HB420RJ, manufactured by Japan Polyethylene Corporation) at 3% by mass, and white master batch at 2% by mass, based on the mass of the sheet, and fed to a sheet molding machine (manufactured by LAB TECH Engineering Co., Ltd.), melted at a melting temperature of 150°C to 200°C, and then extruded to form a sheet. No drawdown was observed in the obtained sheet.
[0079] For the molded sheet in Example 5, the dimensional change rate was measured by the measurement method explained in 2.(1) above. The results of the dimensional change rate in the long side direction of the sheet are shown in Table 1. The results of the dimensional change rate in the short side direction of the sheet are shown in Table 2. Note that the measurements in each direction were performed with an N number of 4, and the arithmetic average value was used. Furthermore, the change in the dimensional change rate in the long side direction of the sheet over time is shown in Figure 2. The change in the dimensional change rate in the short side direction of the sheet over time is shown in Figure 3.
[0080] [Table 1]
[0081] [Table 2]
[0082] [Comparative Example 1]
[0083] A masterbatch was obtained in the same manner as in Example 1, except that corn starch was used instead of scallop shell powder. The obtained masterbatch was used to mold a sheet in the same manner as in Example 5. The dimensional change rate in the long side direction and short side direction of the obtained sheet was measured in the same manner as in Example 5. The respective measurement results are shown in Tables 1 and 2. The change over time in the dimensional change rate in the long side direction of the sheet is shown in Figure 2. The change over time in the dimensional change rate in the short side direction of the sheet is shown in Figure 3.
[0084] These results show that the sheet of Example 5 undergoes almost no dimensional change over time compared to the sheet of Comparative Example 1.
[0085] [Example 6]
[0086] A three-layer structure film having a total thickness of 45 μm was molded using a multi-layer inflation molding machine (Hokushin Sangyo Co., Ltd., die size: 350φ, extruder diameter (inner layer: 65 mm, middle layer: 90 mm, outer layer: 65 mm), cylinder temperature: 165°C, die temperature: 184°C) according to the formulation in Table 3 below. The master batch of Example 4 was diluted with linear low-density polyethylene resin (product name: Novatec (registered trademark) LL UF641, manufactured by Japan Polyethylene Co., Ltd.) so that the content of scallop shell powder in the middle layer was 40 mass%. The thicknesses of the inner layer, middle layer, and outer layer were 15 μm:15 μm:15 μm, respectively.
[0087] [Table 3]
[0088] In Example 6, the surface roughness (Ry, Ra, Rz) in the MD direction of the three-layer structure film was measured by the measurement method described in 2.(1) above. The results of the surface roughness (Ry, Ra, Rz) are shown in Table 4. The measurement was performed on three samples, and the arithmetic average value was used.
[0089] [Table 4]
[0090] [Comparative Example 2]
[0091] A three-layer structure film was molded in the same manner as in Example 6, except that a linear low-density polyethylene resin (product name: Novatec (registered trademark) LL UF641, manufactured by Japan Polyethylene Corporation) was used for the middle layer and outer layer instead of the master batch of Example 4. The surface roughness (Ry, Ra, Rz) of the obtained three-layer structure film was measured in the same manner as in Example 6. The results of the surface roughness (Ry, Ra, Rz) are also shown in Table 4. The measurement was performed on 3 samples, and the arithmetic average value was used.
[0092] As shown in Table 4, the three-layer structure film of Example 6 had a surface roughness (Ry) of 7 μm or more, whereas the three-layer structure film of Comparative Example 2 had a surface roughness (Ry) of less than 7 μm.
[0093] [Example 7]
[0094] 1.Masterbatch manufacturing
[0095] A master batch (hereinafter referred to as the master batch of Example 7) was obtained in the same manner as in Example 2, except that a polypropylene resin (product name: Qualia (registered trademark) CS356M, manufactured by SunAllomer Co., Ltd.) was used instead of the polypropylene resin used in Example 1. The content of scallop shell powder in the obtained master batch of Example 7 was 70 mass%.
[0096] 2. Manufacturing of multi-layer sheets
[0097] According to the formulation in Table 5 below, the masterbatch of Example 7, polypropylene resin (product name: EA9, manufactured by Japan Polypropylene Corporation), polypropylene resin (product name: BC6C, manufactured by Japan Polypropylene Corporation), talc, additives, lubricant, and white masterbatch were supplied to a middle layer extruder 302 of a multi-layer co-extrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in FIG. 4 via a hopper (not shown).
[0098] According to the composition in Table 5 below, polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) was supplied to the extruder 301 for outer layer 1 of the multi-layer coextrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in Figure 4 via a hopper (not shown).
[0099] According to the formulation in Table 5 below, polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) was supplied to the extruder 303 for outer layer 2 of the multilayer coextrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in Figure 4 via a hopper (not shown). The resin compositions supplied to the extruder for outer layer 1, the extruder for middle layer, and the extruder for outer layer 2 were coextruded to obtain a multilayer sheet with a three-layer structure having a thickness of 580 μm. The thickness of the outer layer 1 was 15 μm, the thickness of the middle layer was 550 μm, and the thickness of the outer layer 2 was 15 μm.
[0100] The content of the master batch of Example 7 relative to the total mass of the sheet was 13.8 mass%, the content of polypropylene resin (product name: EA9, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 39.9 mass%, the content of polypropylene resin (product name: BC6C, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 17.1 mass%, the content of talc relative to the total mass of the sheet was 19.2 mass%, the content of lubricant relative to the total mass of the sheet was 0.1 mass%, the content of additives relative to the total mass of the sheet was 0.1 mass%, the content of white master batch relative to the total mass of the sheet was 1.8 mass%, and the content of polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 7.9 mass%.
[0101] The cylinder temperature and adapter temperature of the extruder 301 for outer layer 1 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm), the extruder 302 for middle layer (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm), and the extruder 303 for outer layer 2 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm) were each set to 200° C. The screw speed of the extruder 302 for middle layer was set to 90 RPM, and the screw speed of the extruder 301 for outer layer 1 and the extruder 303 for outer layer 2 were each set to 20 RPM.
[0102] [Table 5]
[0103] [Example 8]
[0104] According to the formulation in Table 6 below, the masterbatch of Example 7, polypropylene resin (product name: EA9, manufactured by Japan Polypropylene Corporation), polypropylene resin (product name: BC6C, manufactured by Japan Polypropylene Corporation), talc, additives, lubricant, white masterbatch, and antioxidant were supplied to a middle layer extruder 302 of a multi-layer co-extrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in FIG. 4 via a hopper (not shown).
[0105] According to the formulation in Table 6 below, polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) was supplied to the extruder 301 for outer layer 1 of the multi-layer coextrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in Figure 4 via a hopper (not shown).
[0106] According to the formulation in Table 6 below, polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) was supplied to the extruder 303 for outer layer 2 of the multilayer coextrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in Figure 4 via a hopper (not shown). The resin compositions supplied to the extruder for outer layer 1, the extruder for middle layer, and the extruder for outer layer 2 were coextruded to obtain a multilayer sheet with a three-layer structure having a thickness of 580 μm. The thickness of the outer layer 1 was 15 μm, the thickness of the middle layer was 550 μm, and the thickness of the outer layer 2 was 15 μm.
[0107] The content of the master batch of Example 7 relative to the total mass of the sheet was 14.2 mass%, the content of polypropylene resin (product name: EA9, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 34.2 mass%, the content of polypropylene resin (product name: BC6C, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 3.8 mass%, the content of talc relative to the total mass of the sheet was 40.4 mass%, the content of lubricant relative to the total mass of the sheet was 0.3 mass%, the content of additives relative to the total mass of the sheet was 0.2 mass%, the content of white master batch relative to the total mass of the sheet was 1.7 mass%, the content of antioxidant relative to the total mass of the sheet was 0.1 mass%, and the content of polypropylene resin (product name: EG6D, manufactured by Japan Polypropylene Corporation) relative to the total mass of the sheet was 5.2 mass%.
[0108] The cylinder temperature and adapter temperature of the extruder 301 for outer layer 1 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm), the extruder 302 for middle layer (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm), and the extruder 303 for outer layer 2 (model number: LE25-30 / C (manufactured by LAB TECH Engineering), L / D: 30, φ: 250 mm) were each set to 200° C. The screw speed of the extruder 302 for middle layer was set to 90 RPM, and the screw speed of the extruder 301 for outer layer 1 and the extruder 303 for outer layer 2 were each set to 20 RPM.
[0109] [Table 6]
[0110] The present invention can also adopt the following configuration. [1] A master batch comprising an inorganic powder, a thermoplastic resin, and a metal soap. [2] The specific gravity of the inorganic powder is 2.5 g / cm 3 The masterbatch according to [1] above. [3] The masterbatch according to [1] or [2], wherein the inorganic powder is shell powder. [4] The masterbatch according to [3], wherein the shell powder is scallop shell powder. [5] The masterbatch according to [1] or [2], wherein the inorganic powder is a mineral powder. [6] The masterbatch according to [5], wherein the mineral powder is a clay mineral powder. [7] The masterbatch according to [6], wherein the clay mineral powder is a talc powder. [8] The masterbatch according to any one of [1] to [7], wherein the thermoplastic resin has an MFR of 50 or less. [9] The master batch according to any one of [1] to [8], wherein the content of the inorganic powder is 10 mass % or more based on the mass of the master batch.
[10] A molded body formed from a kneaded mixture containing an inorganic powder, a thermoplastic resin, and a metal soap.
[11] The specific gravity of the inorganic powder is 2.5 g / cm 3 The molded article according to
[10] above.
[12] The molded body according to
[10] or
[11] , wherein the inorganic powder is shell powder.
[13] The molded body according to
[10] or
[11] , wherein the inorganic powder is a mineral powder.
[14] The molded body according to
[13] , wherein the mineral powder is a clay mineral powder.
[15] The molded article according to any one of
[10] to
[14] , which has a dimensional change rate of 0.2% or less when left for one day in an environment at a temperature of 23° C. and a humidity of 50%.
[16] The molded article according to any one of
[10] to
[15] , which has a dimensional change of 0.2% or less when placed in an environment having a temperature of 23° C. and a humidity of 50% for 3 days.
[17] The molded article according to any one of
[10] to
[16] , wherein at least one surface has a surface roughness (Ry) of 7 μm or more.
[18] A method for producing a masterbatch using an extruder, comprising the steps of: The extruder includes a first raw material supply port for supplying raw materials of the master batch into a cylinder, a first kneading section provided downstream of the first raw material supply port and kneading the raw materials, a first vacuum vent port provided downstream of the first kneading section, a second kneading section provided downstream of the first raw material supply port and kneading the raw materials kneaded in the first kneading section, a second vacuum vent port provided downstream of the second kneading section, a third kneading section provided downstream of the second vacuum vent port and kneading the raw materials kneaded in the second kneading section, and a discharge port for discharging the raw materials kneaded in the third kneading section, The raw materials include an inorganic powder, a metal soap, and a thermoplastic resin, the first raw material supply port supplies the inorganic powder, the metal soap, and the thermoplastic resin; A method for producing a masterbatch, wherein the degree of kneading in the second kneading zone is stronger than the degree of kneading in the first kneading zone.
[19] The method for producing a masterbatch according to
[18] , wherein the extruder further comprises a second raw material supply port provided downstream of the first vacuum vent port and for supplying raw materials for the masterbatch.
[20] The method for producing a masterbatch according to
[18] or
[19] , wherein the second raw material supply port supplies the inorganic powder and the metal soap.
[0111] The configurations, methods, steps, shapes, materials, and values described in the above-described embodiments and examples are merely examples, and different configurations, methods, steps, shapes, materials, and values may be used as necessary.
[0112] Furthermore, the configurations, methods, steps, shapes, materials, numerical values, etc. of the above-described embodiments and examples can be combined with each other without departing from the spirit of the present invention.
[0113] In addition, in this specification, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In a numerical range described in stages in this specification, the upper limit or lower limit of a numerical range in a certain stage may be replaced with the upper limit or lower limit of a numerical range in another stage. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types.
Claims
1. A master batch comprising an inorganic powder, a thermoplastic resin, and a metal soap.
2. The specific gravity of the inorganic powder is 2.5 g / cm 3 The masterbatch according to claim 1 .
3. 2. The masterbatch of claim 1, wherein the inorganic powder is shell powder.
4. 4. The masterbatch of claim 3, wherein the shell powder is scallop shell powder.
5. 2. The masterbatch of claim 1, wherein the inorganic powder is a mineral powder.
6. 6. The masterbatch of claim 5, wherein the mineral powder is a clay mineral powder.
7. 7. The masterbatch according to claim 6, wherein the clay mineral powder is a talc powder.
8. 2. The masterbatch according to claim 1, wherein the thermoplastic resin has an MFR of 50 or less.
9. The masterbatch according to claim 1 , wherein the content of the inorganic powder is 10% by mass or more based on the mass of the masterbatch.
10. A molded body formed from a kneaded mixture containing an inorganic powder, a thermoplastic resin, and a metal soap.
11. The specific gravity of the inorganic powder is 2.5 g / cm 3 The molded article according to claim 10 .
12. The molded body according to claim 10, wherein the inorganic powder is shell powder.
13. The molded body according to claim 10, wherein the inorganic powder is a mineral powder.
14. The molded body according to claim 13, wherein the mineral powder is a clay mineral powder.
15. The molded article according to claim 10, which has a dimensional change of 0.2% or less when placed in an environment having a temperature of 23° C. and a humidity of 50% for one day.
16. The molded article according to claim 10, which has a dimensional change of 0.2% or less when placed in an environment having a temperature of 23° C. and a humidity of 50% for 3 days.
17. The molded article according to claim 10, having a surface roughness (Ry) of 7 μm or more on at least one surface.
18. A method for producing a masterbatch using an extruder, comprising the steps of: The extruder includes a first raw material supply port for supplying raw materials of the master batch into a cylinder, a first kneading section provided downstream of the first raw material supply port and kneading the raw materials, a first vacuum vent port provided downstream of the first kneading section, a second kneading section provided downstream of the first raw material supply port and kneading the raw materials kneaded in the first kneading section, a second vacuum vent port provided downstream of the second kneading section, a third kneading section provided downstream of the second vacuum vent port and kneading the raw materials kneaded in the second kneading section, and a discharge port for discharging the raw materials kneaded in the third kneading section, The raw materials include an inorganic powder, a metal soap, and a thermoplastic resin, the first raw material supply port supplies the inorganic powder, the metal soap, and the thermoplastic resin; A method for producing a masterbatch, wherein the degree of kneading in the second kneading section is stronger than the degree of kneading in the first kneading section.
19. The method for producing a masterbatch according to claim 18, wherein the extruder further comprises a second raw material supply port provided downstream of the first vacuum vent port and for supplying raw materials for the masterbatch.
20. The method for producing a masterbatch according to claim 18 , wherein the second raw material supply port supplies the inorganic powder and the metal soap.
Citation Information
Patent Citations
Synthetic resin composition containing scallop shell
JP2004075964A
Resin composition and foaming-molded product
JP2010106270A